`12 + 5k = 15 - 4k`

Add 4k to each side.

`12 + 9k = 15`

Subtract 12 from each side.

`9k = 3`

Divide both sides by 9.

`k = 3/9 = 1/3`

**The solution is k = `1/3.`**

**Check your solution......................**

`12 + 5(1/3) = 15 - 4(1/3)`

`12 + 5/3 = 15 - 4/3`

Since 12 = `36/3` and 15 = `45/3` , we have

`36/3 + 5/3 = 45/3 - 4/3`

`41/3 = 41/3`

The solution works.

`12+5k =15-4k`

`12+5k+4k =15`

`5k+4k =15-12`

`9k =3`

`k=3/9`

`k=1/3` or equivalent ` k=0.(3)`

First, one needs to have on the left side of the equality the unknown terms and on the right side the known values. Thus we add `+4k` both to the left and to the right of the equality.

Then to have on the right side only known numbers, we add both to the left and to the right of the equality the number `-12` .

Finlay we divide by `9` both sides and simplify both the numerator and the denominator with `3` .

**Answer: From the above equality we obtain `k=1/3` **